Complete abolition of child labour : a possibility - Jain, Mahaveer (New Delhi, 2006)
The present volume provides insights into the processes of securing hundred percent abolition of child labour and strategies to retain hundred percent enrolment of children below the age of 14 in the schools. It gives practical and ground realities as to how child labour problem can be tackled without addressing the issues of poverty and welfare. This volume depicts a unique feature which has been achieved by the collective efforts and convergence of various departments of the government of Andhra Pradesh at the mandal/tehsil and district levels. This volume deals with the gigantic issue of child labour which is nearly impossible to eliminate. It shows that it is possible to eliminate hundred percent child labour with minimal financial support and through the existing administrative and developmental resources. It is strongly believed that the volume would definitely help all the persons, students, departments, and organizations working on the issue of child labour and all those who are making all out efforts to send all the children below 14 years to schools for their future growth and development.
Keywords: Child labour abolition